Cooling and exhumation history of the northeastern Gawler Craton, South Australia - Forbes, C.; Giles, D.; Jourdan, Fred; Sato, K.; Omori, S.; Bunch, M. (Elsevier BV, 2012)
We present biotite 40Ar/39Ar ages and from the Palaeo- to Mesoproterozoic Mount Woods Inlier in the northeastern Gawler Craton, South Australia. In combination with garnet–biotite Fe–Mg exchange modelling using the THERMAL HISTORY program, these data are used to constrain a post-peak metamorphic P–T path, cooling rates and a temperature–time path for the inlier. Consistently well-defined plateaus at ~1.53 Ga of biotite 40Ar/39Ar age spectra indicate that the rocks cooled through ~300 °C at this time. Cooling rates within the inlier are ~3–9 °C/Ma from peak high-temperature/low-pressure metamorphism at ~1.59 Ga to ~1.53 Ga. Cooling rates subsequently decreased to ~4 °C/Ma. Cooling is suggested to be a function of cessation of voluminous magmatism and mantle heat input in conjunction with exhumation initiated along the southwestern margin of the inlier ca. 1.592–1.582 Ga. The temperature–time path of the inlier has a concave shape. The peak metamorphic and ensuing cooling history of the Mount Woods Inlier are akin to the nearby Curnamona Province, Coober Pedy Ridge and Mabel Creek Ridge within the South Australian Craton. Deformation during high-grade metamorphism within these terranes was accommodated at mid-crustal levels, and large-scale exhumation did not occur until the terranes cooled and were able to be exhumed as coherent, rigid blocks along discrete shear zones and faults.